Existential Anxiety and Spatial Reconstruction in Mohsin Hamid’s Exit West - Baturay Erdal (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Existentialists, while seeking meaning within the depths of human existence, examine human freedom, responsibilities, and choices. As individuals are responsible for every choice they make, a state of anxiety emerges as an intrinsic part of their existence during these choices. Meanwhile, space serves as the stage upon which human beings exist and navigate their existential journey, marked by these very responsibilities and decisions. In his novel Exit West (2017), British Pakistani writer Mohsin Hamid addresses the issue of migration, which has become a global problem today, rendering the existential journeys of the protagonists Nadia and Saeed to produce a literary solution to this global issue. He invites his readers to witness not only a story of migration but also an existential journey through the magic doors he opens by using magical realism in the novel. He problematizes borders as the greatest locus of the age and facticity in the existential sense. Consequently, he attempts to demonstrate how this anxiety can be transcended in various spaces constructed using the magical realism technique. Each space reconstructed by the author promises new opportunities for the characters to make sense of their existence on the path to authenticity. Thus, the anxiety-inducing boundaries of geographical borders become an existential issue in the novel, while the imaginary line between ontological space and physical place disappears.